Advances and Impacts of the Theory of Inventive Problem Solving : The TRIZ Methodology, Tools and Case Studies - Koziołek, Sebastian; Chechurin, Leonid; Collan, Mikael (Springer International Publishing, 2018)
This book offers a collection of cutting-edge research on the Theory of Inventive Problem Solving (TRIZ). Introduced by Genrich Altshuller in 1956, TRIZ has since been used by engineers, inventors and creators as an essential structured innovation method at businesses and organizations around the globe. The chapters of this book showcase work by selected authors from the 'TRIZ Future' conferences, which are organized by the European TRIZ Association (ETRIA). The chapters reflect an international mix of new ideas on TRIZ and knowledge-based innovation, highlight recent advances in the TRIZ community, and provide examples of successful collaboration between industry and academia. The book first introduces the reader to recent methodological innovations, then provides an overview of established and new TRIZ tools, followed by a collection of case studies and examples of TRIZ implementation in various scientific and social contexts.